Truman Capote papers - Capote, Truman, 1924-1984.; Capote, Truman, 1924-1984.; Capote, Truman, 1924-1984.; Capote, Truman, 1924-1984.
Chiefly literary manuscripts including drafts and manuscripts of prose fiction, dramas, and screenplays as well as journals, notebooks, and other writings. Includes drafts of Capote's novels, Other Voices, Other Rooms (1948), Breakfast at Tiffany's : A Short Novel and Three Stories (1958), and In Cold Blood : A True Account of a Multiple Murder and Its Consequences (1965); the musical play, "House of Flowers" (1954); the short story, "A Christmas Memory" (1956); and a profile of Marlon Brando, "The Duke in His Domain" (1957).
Library of Congress Prints and Photographs Division.
Author and dramatist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brando, Marlon; American fiction; American literature; Drama; Fiction; Literature; Motion picture plays; Musicals; Short stories; Authors; Dramatists